2005
DOI: 10.1080/09670870500228529
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pseudostem and pheromone seasonal trapping of the banana weevilCosmopolites sordidusin South Africa

Abstract: The banana weevil (Cosmopolites sordidus) is an important pest of bananas (Musaceae: Musa species) in South Africa. Adult trapping methods were compared in field trials using a randomised block design. Pseudostem traps, pitfall traps containing a pheromone (either Cosmolure Õ (Pheromone A) or Cosmolure+ Õ (Pheromone B)), and unbaited pitfall traps (control), were compared over 5 weeks during all seasons along the Southeast coast of South Africa. Pseudostem traps treated with an insecticide, and rhizome traps, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
(35 reference statements)
2
6
0
4
Order By: Relevance
“…The present study shows that the two baits were almost equally attractive to adult weevils in the range 0–10 m, whereas the pheromone bait was more efficient in the range 10–100 m. The greater effect of pheromones in attracting weevils compared with pseudostem material has been reported previously (Jayaraman et al , 1997; De Graaf et al , 2005). By contrast, Tinzaara et al (2007b) found no significant difference between fresh pseudostem and pheromone (Cosmolure+; ChemTica Int., Costa Rica) attractiveness to adult weevils.…”
Section: Discussionsupporting
confidence: 83%
“…The present study shows that the two baits were almost equally attractive to adult weevils in the range 0–10 m, whereas the pheromone bait was more efficient in the range 10–100 m. The greater effect of pheromones in attracting weevils compared with pseudostem material has been reported previously (Jayaraman et al , 1997; De Graaf et al , 2005). By contrast, Tinzaara et al (2007b) found no significant difference between fresh pseudostem and pheromone (Cosmolure+; ChemTica Int., Costa Rica) attractiveness to adult weevils.…”
Section: Discussionsupporting
confidence: 83%
“…Baiting pseudostem traps with sordidin released at one milligram per day increased capture rates by eight fold, while white pitfall traps containing soapy water and from which sordidin was released at one milligram per day captured about two and a half times more C. sordidus than similarly sordidin-baited pseudostem traps (Jayaraman et al, 1997). Several studies have confirmed the efficacy of sordidinbaited pitfall traps (Tinzaara et al, 1999;de Graaf et al, 2005). A more recent study demonstrated that crawl-in ground traps outperform pitfall traps (Reddy et al, 2009), and that traps are more effective in the shade (Reddy et al, 2008(Reddy et al, , 2009).…”
Section: Introductionmentioning
confidence: 84%
“…Speijer et al (1993) only found a correlation between numbers of male weevils caught with pseudostem trap in a plot and the mean percent of infestation measured in the plot. De Graaf et al (2005) found that less than 20% of the total of pheromone traps catch comprised females with eggs, yet only this category can damage the rhizome.…”
Section: Discussionmentioning
confidence: 99%
“…In 1993, Budenberg et al (1993b) identified the aggregation pheromone emitted by C. sordidus males, and Beauhaire et al (1995) further developed the equivalent synthetic pheromone called ‘Sordidine’. Subsequent to 1999, traps with Sordidine, formulated by ChemTica International (Costa Rica), have been tested under field conditions in Costa Rica (Alpizar et al , 1999), Uganda (Tinzaara et al , 1999) and South Africa (De Graaf et al , 2005). The pheromone traps are more effective than pseudostem traps.…”
Section: Introductionmentioning
confidence: 99%